In vitro starch digestibility, cooking quality, rheology and sensory properties of gluten-free pregelatinized rice noodle enriched with germinated chickpea flour. (November 2020) - Sofi, Sajad Ahmad; Singh, Jagmohan; Mir, Shabir Ahmad; Dar, B.N.
Abstract: Physicochemical, rheological, in vitro digestibility, and sensory characteristics of the gluten-free noodles made of pregelatinized rice flour incorporated with germinated chickpea flours (5, 10, 20 and 30 g/100 g) were investigated. The addition of germinated chickpea flour from two cultivars (GNG 1581 and GNG469) in gluten free noodles significantly (p < 0.05) enhanced crude protein level (7.52–10.5 g/100 g), crude fiber (1.3–4.4 g/100 g), amylose (21.2–25.9 g/100 g), antioxidant activity (22.8–34.5 g/100 g), total phenolic acids (117.7–203.04 mg GAE/100 g) and in vitro protein digestibility (78.7–84.9%) of prepared noodles. These noodles had low lightness value due to the presence of the color components. The gluten free noodles showed a significant reduction in glycemic index (70.83–61.79) with better cooking quality. Dough rheology of noodles developed showed pseudoplastic behaviour (Gʹ > Gʺ) with an increase in storage and loss modulus. Protein bands ranged from 10 to 250 kDa with a difference in band intensities observed in gluten free noodles. In sensory evaluation, overall acceptance of noodles containing germinated chickpea flour was highest at 20 g/100 g level of incorporation and was acceptable up to 30 g/100 g level of chickpea flour incorporation. Graphical abstract: Image 1 Highlights: Gluten free noodle produced with pregelatinized rice and germinated chickpea flour. Noodle enriched with germinated chickpea flour improved their nutritional quality. Germinated chickpea improved protein digestibility and lower glycemic index. Germinated chickpea flour improved cooking qualities of noodles. Noodle with 20% of germinated chickpea flour showed better sensory acceptability.